Invisible Gold Paragenesis and Geochemistry in Pyrite from Orogenic and Sediment-Hosted Gold Deposits - Large R.R.; Maslennikov V.V. (My University, 2020)
LA-ICPMS analysis of pyrite in ten gold deposits is used to determine the precise siting of invisible gold within pyrite, and thus the timing of gold introduction relative to the growth of pyrite and related orogenic events. A spectrum of invisible gold relationships in pyrite has been observed which suggests that, relative to orogenic pyrite growth, gold introduction in some deposits is early at the start of pyrite growth; in other deposits, it is late toward the end of pyrite growth and in a third case, it may be introduced at the intermediate stage of orogenic pyrite growth. In addition, we report a distinct chemical association of invisible gold in pyrite in the deposits studied. For example, in the Gold Quarry (Carlin type), Mt Olympus, Macraes and Konkera, the invisible gold is principally related to the arsenic content of pyrite. In contrast, in Kumtor and Geita Hill, the invisible gold is principally related to the tellurium content of pyrite. Other deposits (Golden Mile, Bendigo, Spanish Mountain, Witwatersrand Carbon Leader Reef (CLR)) exhibit both the Au-As and Au-Te association in pyrite. Some deposits of the Au-As association have late orogenic Au-As-rich rims on pyrite, which substantially increase the value of the ore. In contrast, deposits of the Au-Te association are not known to have Au-rich rims on pyrite but contain nano- to micro-inclusions of Au-Ag-(Pb-Bi) tellurides.
Keywords: invisible gold; refractory gold; arsenic; tellurium; orogenic gold; Witwatersrand gold; Carlin deposits; LA-ICPMS; laser mapping